Patient Safety Curriculum for Anatomic Pathology Trainees: Recommendations Based on Institutional Experience. (March 2016) - Samulski, Teresa D.; Montone, Kathleen; LiVolsi, Virginia; Patel, Ketan; Baloch, Zubair
Abstract : Because of the unique systems and skills involved in patient care by the pathologist, it is challenging to design and implement relevant training in patient safety for pathology trainees. We propose a patient safety curriculum for anatomic pathology (AP) residents based on our institutional experience. The Hospital of the University of the Pennsylvania employs a self-reporting safety database. The occurrences from July 2013 to June 2015 recorded in this system that involved the division of AP were reviewed and cataloged as preanalytic, analytic, and postanalytic. The distribution of these occurrences was then used to create a framework for curriculum development in AP. We identified areas in which trainees are involved in the identification and prevention of common patient safety errors that occur in our AP department. Using these data-proven target areas, and employing current Accreditation Council for Graduate Medical Education recommendations and patient safety literature, a strategy for delivering relevant patient safety training is proposed. Teaching patient safety to pathology trainees is a challenging, yet necessary, component of AP training programs. By analyzing the patient safety errors that occur in the AP department, relevant and actionable training can be developed. This provides quality professional development and improves overall performance as trainees are integrated into laboratory systems.